Perception of facial expressions of emotion in migraine - Rashidi, Mahmoud; Oelkers-Ax, Rieke; Sharma, Anuradha; Bertsch, Katja; Weisbrod, Matthias (Brain research, 2018)
Both lower-level perceptual changes and especially higher-level cognitive alterations in individuals with migraine are poorly understood.